2009
DOI: 10.1158/0008-5472.can-09-2341
|View full text |Cite
|
Sign up to set email alerts
|

Natural Sphingadienes Inhibit Akt-Dependent Signaling and Prevent Intestinal Tumorigenesis

Abstract: Sphingolipid metabolites regulate cell proliferation, migration, and stress responses. Alterations in sphingolipid metabolism have been proposed to contribute to carcinogenesis, cancer progression, and drug resistance. We identified a family of natural sphingolipids called sphingadienes and investigated their effects in colon cancer. We find that sphingadienes induce colon cancer cell death in vitro and prevent intestinal tumorigenesis in vivo. Sphingadienes exert their influence by blocking Akt translocation … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
60
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(61 citation statements)
references
References 40 publications
1
60
0
Order By: Relevance
“…Previous work pointed out the importance of sphingolipids in the regulation of autophagy (56 -58). Indeed, manipulation of sphingolipid metabolic enzymes modulates autophagy in various systems (22,34,49,(52)(53)(54). We speculate that pharmacologic inhibition of Sphk isoenzymes could lead to intracellular sphingolipid accumulation and compensatory autophagic responses in cells with high flux in the sphingolipid metabolic pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Previous work pointed out the importance of sphingolipids in the regulation of autophagy (56 -58). Indeed, manipulation of sphingolipid metabolic enzymes modulates autophagy in various systems (22,34,49,(52)(53)(54). We speculate that pharmacologic inhibition of Sphk isoenzymes could lead to intracellular sphingolipid accumulation and compensatory autophagic responses in cells with high flux in the sphingolipid metabolic pathways.…”
Section: Discussionmentioning
confidence: 99%
“…We next asked whether it was possible to reverse SPL downregulation in the gut, thus making it a potential target for chemoprevention. We recently reported the chemopreventive activity of SDs, compounds derived from the metabolism of sphingolipids in soy and other nonmammalian food sources (32,33). SDs are cytotoxic to colon cancer cells and reduce adenoma formation when administered orally to Apc Min/+ mice (32,33).…”
Section: Discussionmentioning
confidence: 99%
“…We recently reported the chemopreventive activity of SDs, compounds derived from the metabolism of sphingolipids in soy and other nonmammalian food sources (32,33). SDs are cytotoxic to colon cancer cells and reduce adenoma formation when administered orally to Apc Min/+ mice (32,33). To address the effects of SDs in colitis, we evaluated colon S1P levels in WT mice treated with 25 mg/kg SD (or vehicle alone) by gavage for 6 days.…”
Section: Discussionmentioning
confidence: 99%
“…It is unknown what portion of 4,8-SD becomes bioavailable in the mucosal cells of the intestines after ingestion of complex SLs. However, it was reported that sphingadienines in general have the advantage over other SLs of being slowly metabolized and of having a long half-life in intestinal epithelial cells (21).…”
Section: Discussionmentioning
confidence: 99%